MAHATHIR AND THE SUCCESS OF MALAYSIA - Ahmad Zaidi Johari; Zainal Abidin Ahmad; Ahmad Othman; Sulaiman Hasan; NizamuddinHissuddin; Elizabeth M. Anthony (Penerbit UTHM, 2005)
Malaysia has every reason to be proud of Tun Dr. Mahathir who manouvred Malaysia out of imminent crisis that had hit Malaysian badly. This book is compiled to pay tribute to an extraordinary medical doctor turned world renowned leader, a man who became more than a Prime Minister. He was a man whose voice was heard loud, clear and in whom the world saw a leader held in admiration. Technological advancement, nation development and success have always been his forte and vision. This incredible man continuously believed and strived for ‘Malaysia Boleh’.